(untitled) (Herald of the National Children’s Medical Center, 2025)
To assess the effectiveness of the Synacthen test in diagnosing secondary, tertiary or iatrogenic adrenal insufficiency, as well as non-classic congenital adrenal hyperplasia (NCCAH).